Consciência corporal e gênero: uma experiência com narrativas de alun@s - Dantas, Jacqueline Duarte (2012)
This research was made possible by the Graduate School of Education of the Federal University of Paraiba. The field research is related to Gender Studies. The thesis deals with the interpretation of questions related to the physical body and how it reflects culturally on gender among adolescents. The experiment was conducted in 2005 during Physical Education classes and focused on analyzing Corporeal Consciousness. The subject of Corporeal Consciousness has versatile uses related to studies in Education, and is a means to understanding gender relationships amongst adolescents. Corporeal Consciousness is imprinted in our bodies from before birth and continues on throughout our lifetimes. From a study group of 43 adolescents, 73 statements were analyzed. These autobiographical accounts were written by pre-university students of Collegial Imaculada Conceição in Natal (RN) regarding Physical Education activities in class. The project itself was called Know Yourself ( Conhecer-se ). For this dissertation I chose the autobiographic method called escrita de si (self written). The first chapter is about my own escrita de si experience including memories and recollections that mirror experiences undergone by referenced authors. These writers and I believe that a teacher s life is defined by their teaching methods and how those approaches intertwine with their students lives. This work presents reflections about body and gender, through analysis and categorization of previously mentioned gathered statements as well as discourse among other authors. Through this work, we can see an amplification of the pre-conceptual view of men and women s social roles that come from our bodies, senses, feelings and emotions. This thesis proposes ways to better view and relate to people and things around us, which would lead to education guided by love, as professed by Paulo Freire.